Effectiveness of implementation of the method pedagogical system of forming the experience of music-pedagogical activity of the future music art teachers - Maryna Mykhaskova (Kazimierz Wielki University, 2019)
The article analyzes of forming the experience of music-pedagogical activity of the future teacher of music art. Diagnosis of the experience of music-pedagogical activity of the future music art teacher by the criteria (completeness, systematic and strength of knowledge based on the formedness of professional-pedagogical and innovative thinking; the level of formedness of experience of using the methods of music-pedagogical activity; presence of emotional-value attitude to music-pedagogical activity; intensification of communication on the basis of joint interaction of the participants of music-pedagogical activity; level of ability to predict, analyze, control and adjust music-pedagogical activity; originality of creative experience in various types of music-pedagogical activity) and indicators allows to evaluate the level of its formedness, to predict approaches, conditions and directions of improving the effectiveness of professional training of pedagogues-musicians. The feasibility of the chosen system of training of the future teachers of music art has been grounded. It is based on the structural and functional components of the process, provides for the realization of clearly defined principles, conditions, methodological and methodical principles. It is determined that the introduction of the special course "Art Workshop" allows improving the results of professional training of the future pedagogues-musicians. The offered course includes lectures, practical classes, seminars, independent work, teaching and control methods, approximate evaluation of students' educational activities by rating system, distribution of points received by students in the course of mastering the special course "Art Workshop", the scale of assessment according to the national and ECTS system, methodological support of the special course, recommended literature, information resources of the discipline.